Weather Reports for Research Field Locations - M. Knapp (Kansas Agricultural Experiment Station Research Reports, 2017)
Weather Reports for Research Field Locations in Kansas 2016: Ashland Bottoms, Belleville, Colby, Conway Springs, Ellsworth, Hays, Hutchinson, Manhattan, McPherson, Perry and Scandia.
Keywords: weather